ANALISIS AKUNTABILITAS DAN TRANSPARANSI PEMERINTAH DESA DAN PARTISIPASI MASYARAKAT DESA DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (STUDI PADA ALOKASI DANA DESA TAHUN ANGGARAN 2016 DI DESA BALAI AGAS KECAMATAN BELIMBING KABUPATEN MELAWI) - ana, MARSIANA B1031131135 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
ABSTRACTThe purpose of this research is to know how the transparency, accountability and participation of Balai Agas village community in village fund management. The research type used qualitative descriptive method by using primary data and secondary data that collected data with observation technique, interview, documentation and questionnaire distribution. The analysis tool uses the calculation of the results of questionnaire and external analysis that is using fiscal accountability. APBDes Desa Balai Agas 2016 is viewed from the fiscal accountability side seen from sub income and seen from sub-sub expenditure that accountability has been very effective. Government transparency analysis on the community through questionnaires has been transparent, and community participation, showing as much as it has been effective. The results of the transparency and community participation accountability analysis have been in line with the number 113 of 2014.Â Keywords: Accountability, Transparency, Participation, APBDes and Pemendagri number 113 year 2014.Â Â